Do high-PSM public employees like extrinsic rewards? A latent class analysis. Issue 2 (3rd April 2023) - Xu, Chengwei; Mussagulova, Assel; Chen, Chung-An; Kuo, Ming-Feng
ABSTRACT: Scholarship examining public service motivation (PSM) in multi-incentive settings is still insufficient. Though previous studies have extensively tested the nomological networks of PSM, they paid less attention to differences between individual preferences. Drawing on latent class analysis (LCA), this study addresses this gap by focusing on these differences in a multi-incentive setting instead of merely investigating relationships between variables. The analysis established a four-class model that classified 1286 Chinese respondents into four groups based on their PSM level and responses to three types of rewards (i.e., intrinsic, intangible extrinsic, and tangible extrinsic rewards). Results demonstrated that: among the respondents, (1) 32.49% with low PSM preferred tangible extrinsic rewards; (2) 19.3% with moderate PSM showed a preference for intangible extrinsic rewards; (3) 35.94% with high PSM reported a desire for tangible extrinsic rewards; and (4) 12.26% with high PSM showed a preference for all three types of rewards. Findings support the argument that PSM may be compatible with tangible and intangible extrinsic rewards.